Real‐world efficacy and safety outcomes of imatinib treatment in patients with chronic myeloid leukemia: An Australian experience - Josephine A. Adattini; Annette S. Gross; Nicole Wong Doo; Andrew J. McLachlan (Wiley, 2022)
Abstract Tyrosine kinase inhibitors (TKI) have revolutionized the treatment of chronic myeloid leukemia (CML), but patients still experience treatment‐limiting toxicities or therapeutic failure. To investigate the real‐world use and outcomes of imatinib in patients with CML in Australia, a retrospective cohort study of patients with CML commencing imatinib (2001-2018) was conducted across two sites. Prescribing patterns, tolerability outcomes, and survival and molecular response were evaluated. 86 patients received 89 imatinib treatments. Dose modifications were frequently observed (12‐month rate of 58%). At last follow‐up, 62 patients (5‐year rate of 55%) had permanently discontinued imatinib treatment, of which 44 switched to another TKI (5‐year rate of 46%). Within 3 months of starting imatinib, 43% (95% CI, 32%-53%) of patients experienced imatinib‐related grade ≥3 adverse drug reactions (ADRs). Higher comorbidity score, lower body weight, higher imatinib starting dose, and Middle Eastern or North African ancestry were associated with a higher risk of grade ≥3 ADR occurrence on multivariable analysis (MVA). Estimated overall survival and event‐free survival rates at 3 years were 97% (95% CI, 92%-100%) and 81% (95% CI, 72%-92%), respectively. Cumulative incidence of major molecular response (MMR) at 3 years was 63% (95% CI, 50%-73%). On MVA, imatinib starting dose, ELTS score, BCR‐ABL1 transcript type, pre‐existing pulmonary disease, and potential drug-drug interactions were predictive of MMR. In conclusion, imatinib induced deep molecular responses that translated to good survival outcomes in a real‐world setting, but was associated with a higher incidence of ADRs, dose modifications and treatment discontinuations than in clinical trials.